Folding in Miocene, unconsolidated clastic sediments (Vienna basin, Austria) – gravitational versus tectonic forces - Exner, U.; Draganits, E.; Grasemann, B. (TRABAJOS DE GEOLOGÍA, 2009)
Spectacular folded, but virtually unconsolidated sediments in a sand pit in the Vienna basin have been used as one of the key arguments of an E-W shortening event during the Late Miocene in the eastern Alps and western Carpathians. The outcrop has been re-excavated recently and several new observations like the occurrence of refold structures, the fold shapes and the large amount of localized shortening bring into question the established tectonic interpretation. Alternatively, we propose that gravitational forces caused the folding in the frontal part of a slump along the eastern slope of the Vienna basin.